Representations of Angelic beings in early Jewish and in Christian traditions - Amsalu Tefera; Stuckenbruck, Loren T. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Title -- Table of Contents -- Introduction -- Loreen Maseno - An Angel Indeed! Hagar and the Angel in Genesis 16 -- Eshbal Ratzon - The Heavenly Abode of the Luminaries -- Jacques T. A. G. M. van Ruiten - Angelic Authority: Continuities and Transformation in the Angelic World of the Book of Jubilees -- Loren T. Stuckenbruck - In Praise of Angels: The Case of a Wandering Liturgical Fragment -- Matthias Reinhard Hoffmann - Systematic Chaos or Chain of Tradition? References to Angels and 'Magic' in Early Jewish and Early Christian Literature and Magical Writings -- Amsalu Tefera - Angelology of the Ethiopic Homily on Uriel (Dǝrsanä Ura'el) -- Tedros Abraha - The Place of the Angels in the Mäṣḥafä Qəddase (The Book of Hallowing) and in its Andəmta -- Dan Levene - Selling Names: Divine names from the "Homily of Michael" -- Ralph Lee - Little Known Giants Traditions in Ethiopian Literature -- List of Contributors -- Index of Passages -- Index of Modern Authors -- Index of Subjects.